Strategi mitigasi risiko proyek konstruksi utilitas piping dan sipil: Studi kasus PDAM Jakarta - Safruddin MJ; Sawarni Hasibuan (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
Construction activities such as piping and civil works utilities always potentially pose a risk. Therefore, risk management is indispensable for the success of a construction project. The pipeline and Civil works construction project to meet the distribution of clean water needs in Jakarta through the Cooperation Agreement  PDAM Pam Jaya and PT Pam Lyonnaise Jaya (Palyja) potentially generate various risks. The purpose of this research is to analyse risk management on piping and civil works utility construction using the house of risk model.  Research is conducted through two phases. The first phase is the identification of risks and risk agents in the piping and civil works utility construction through the measurement of severity and occurrence levels to produce an aggregate risk priority (ARP), then conducts a risk mitigation analysis in the second phase. 60 respondents involved in the study consisting of project managers, supervisors, and engineers on pipeline and civil works construction projects. The results of the analysis successfully identified 60 risk events and 38 risk agents in the construction of utility piping and work civil PDAM Pam Jaya. FGD and Pareto analysis used in the study produced five recommendations for mitigation actions that are expected to be able to mitigate risk on piping and civil utility construction by establishing QA/QC independently/cooperation, take corrective action (corrective action), conduct testing or testing with the applicable provisions, implement ISO certification of 9001:2015 quality management, and perform training on procedures and standards that apply periodically.